2007
DOI: 10.1016/j.chom.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

To Migrate or to Invade: Those Are the Options

Abstract: Plasmodium sporozoites penetrate and migrate through multiple cells in the host before productively invading a hepatocyte and forming a parasitophorous vacuole. In this issue of Cell Host & Microbe, Coppi and colleagues show that sporozoite interaction with the highly sulfated heparan sulfate proteoglycans on liver cells induces proteolytic cleavage of the major sporozoite surface molecule. They conclude that this interaction is the primary trigger that activates sporozoites for productive invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Sporozoite entry of mammalian cells has been well studied in vitro (60,61) and characterized to include both traversal of cells in which no parasitophorous vacuole is formed and infection of cells accompanied by formation of a parasitophorous vacuole (62)(63)(64)(65). However, the definitive role for the CS protein within this traversal and infection process is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Sporozoite entry of mammalian cells has been well studied in vitro (60,61) and characterized to include both traversal of cells in which no parasitophorous vacuole is formed and infection of cells accompanied by formation of a parasitophorous vacuole (62)(63)(64)(65). However, the definitive role for the CS protein within this traversal and infection process is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria is transmitted by the bite of an infected Anopheles mosquito, which harbors sporozoites in its salivary glands. From the point of injection into the skin, sporozoites migrate via blood vessels to the liver, cross the sinusoidal cell layer separating the blood and the liver, and finally invade hepatocytes where asexual reproduction leads to the release of thousands of merozoites into the bloodstream ( Prudêncio and Mota, 2007 ). Merozoites infect mature red blood cells and, through asexual reproduction, generate daughter merozoites to initiate a new infective cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Following this entry into the space of Disse, sporozoites will often traverse additional hepatocytes before forming a parasitophorous vacuole (PV) during productive invasion of a final hepatocyte and converting into the extra-erythrocytic form (EEF). 26 While the PPLP1 knockout strain was able to form EEF normally in cultured hepatocytes, the number of liver EEF was drastically reduced in vivo during infection but could be restored to wild-type levels by destruction of the Kupffer cells within the sinusoids. 12 Work by Amino et al showed that the kinetics of cell entry strongly favored PV formation by PPLP1 knockout sporozoites, while wild-type controls were more likely to traverse several host cells before forming a PV during cell entry.…”
Section: Structurementioning
confidence: 99%